Intraperitoneal analgesia for laparoscopic cholecystectomy : bupivacaine versus bupivacaine with tramadol - Golubović, Snježana; Golubović, Vesna, liječnica; Cindrić-Stančin, Marija; Sotošek, Vlatka (2009)
Abstract: The type of pain after laparoscopic surgery differs considerably from that seen after laparotomy. Whereas laparotomy results mostly in parietal pain, patients after laparoscopic cholecystectomy complain more of visceral pain results from the stretching of intraabdominal cavity, peritoneal inflammation and phrenic nerve irritation caused by residual carbon dioxide in the peritoneal cavity. Intraperitoneal (IP) administration of some drugs can be effective for pain relief after laparoscopic surgery. The purpose of this study was to asses the effects of intraperitoneal application of bupivacaine or bupivacaine in combination with tramadol on pain relief after laparoscopic cholecystectomy. After informed written consent and local ethic committee approval, ninthy patients of ASA I and II grade undergoing elective laparoscopic cholecystectomy for cholelythiasis were recruited in the study. At the end of laparoscopic cholecystectomy 30 patients in each group received 50 mL saline 0.9% (group C), bupivacaine 0.25% (group B) or bupivacaine 0.25% with tramadol 100 mg (group T). VAS pain was estimated at 30 minutes, 1, 2, 4 and 24 hours after surgery. Postoperative analgesic requires were also assessed. Pain scores were significantly lower in group receiving the IP bupivacaine with tramadol and bupivacaine compared to saline group. Intraperitoneal applications of these drugs reduced consumption of supplementary postoperative analgesic medication. Intraperitoneal administration of bupivacaine with tramadol and bupivacaine are simple to use and effective in a reduction of pain after laparoscopic cholecystectomy. In our study we found no differences between bupivacaine with tramadol and bupivacaine in postoperative VAS score and analgesic requirements
Bibliografija: 17 jed
Sažetak
Keywords: Laparoskopska kolecistektomija -- Laparatomija -- Bol -- Bupivakain -- Tramadol